A Coordinated Framework of DG Allocation and Operating Strategy in Distribution System for Configuration Management under Varying Loading Patterns. Issue 1 (20th January 2020) - Kumar, Pawan; Ali, Ikbal; Thomas, Mini Shaji; Singh, Surjit
Abstract: The distributed generation (DG) planning with the varying pattern of the practical load is difficult as it calls for the frequent changes in DG size and system configuration, which is neither feasible nor permissible. Rather such a DG size and a configuration, which can be utilized over a wider load pattern, are more acceptable. This work presents a coordinated approach for DG planning and system reconfiguration. While to operate a particular DG size and the system configuration over a wide range of loading pattern, the configurations are ranked under different probabilistic loading patterns. Based upon the ranking of the new configuration, the energy performance of the coordinated planning is evaluated. Further, the observations from coordinated planning are imposed on coordinated operation using harmony search algorithm (HSA). The proposed approach is tested for single as well as multi-objectives on a 33-node system. A significant improvement in the computational efforts and energy performance of the resulting configuration have been observed where losses have reduced to 81.11 and 53.77 kW with single DG and multi-DG allocation respectively.